2020
DOI: 10.1002/rcm.8810
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the metabolites of gigantol in rat, dog, monkey, and human hepatocytes using ultra‐high‐performance liquid chromatography coupled with high‐resolution mass spectrometry

Abstract: Rationale: Gigantol (3 0 ,4-dihydroxy-3,5 0 -dimethoxybibenzyl) is a bibenzyl compound isolated from Dendrobii Caulis that has been widely used as a medicinal herb in China. To fully understand the mechanism of action of gigantol, it is necessary to determine its metabolic profile. Methods:Gigantol at a concentration of 20 μM was incubated with hepatocytes (rat, dog, monkey, and human) at 37 C. After 120 min incubation, the samples were analyzed using liquid chromatography coupled with electrospray ionization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The metabolism of stilbenoids has been extensively investigated in previous studies, such as resveratrol (Gambini et al, 2015), erianin (Liu et al, 2020), dihydroresveratrol (Ji et al, 2021) and gigantol (Fan et al, 2014; Wang et al, 2020). Compared with previous studies, pterostilbene showed similar metabolic pathways to other stilbenoids, i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The metabolism of stilbenoids has been extensively investigated in previous studies, such as resveratrol (Gambini et al, 2015), erianin (Liu et al, 2020), dihydroresveratrol (Ji et al, 2021) and gigantol (Fan et al, 2014; Wang et al, 2020). Compared with previous studies, pterostilbene showed similar metabolic pathways to other stilbenoids, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…glucuronidation was the most predominant metabolic pathway. In addition, like erianin (Liu et al, 2020), dihydroresveratrol (Ji et al, 2021) and gigantol (Wang et al, 2020), GSH conjugation (M5 and M6) was also found to be one of the metabolic pathways, suggesting the formation of reactive metabolite. Reactive metabolite has been recognized as one of the causative factors of some drug toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, the metabolism of several stilbenoids has been investigated, including resveratrol, 18,19 erianin 17 and gigantol. 20 The major metabolic pathways of resveratrol were glucuronidation and sulfation. In addition, resveratrol could be metabolized into dihydroresveratrol in human intestinal bacteria.…”
Section: Sample Preparationmentioning
confidence: 99%
“…11,12 The development of high-resolution mass spectrometry has facilitated metabolite identification, which can provide structure-associated information of the parent and metabolites. [13][14][15] There are several publications regarding studies of the metabolism of stilbenoids such as gigantol 16 and erianin .17 To the best of our knowledge, the metabolic fates of batatasin III have not been discovered.…”
Section: Introductionmentioning
confidence: 99%